Building brand perception through message consistency: a qualitative study in the retail industry - Yudith Sitinjak; Nafiah Ariyani (Sean Institute, 2024)
This research aims to analyze the effect of message consistency on brand perception in the retail industry. Message consistency in marketing communications is an important factor that can help consumers understand and remember the brand better and form positive perceptions. This research uses qualitative methods through surveys and interviews with consumers in the retail sector. The research results show that message consistency has a significant influence on brand perception. Consumers tend to have positive perceptions of brands whose messages are consistent across all communication channels. However, this research also found that message consistency is not the only factor that influences brand perception. Other factors such as product quality, customer service, and brand reputation also play an important role. Therefore, it is advisable for retail companies to not only focus on message consistency, but also consider other factors in their marketing strategy. This research contributes to the marketing literature by providing further understanding of how message consistency influences brand perception in the context of the retail industry.